An examination of the role of arts councils in the development of theatre: the case of the National Arts Council of Zimbabwe and Theatre in Harare - Mukanga, Florence (My University, 2009)
ABSTRACT This study brings into critical focus the relationship between the National Arts Council of Zimbabwe (NACZ) as an aspect of the government’s cultural policy and theatre in Harare. It demonstrates that the birth and well being of the NACZ has been shaped by global and African perspective of arts councils as well as politics in form of colonisation and decolonisation processes. It argues that the NACZ played an influential role in the development of theatre before 1995, mostly through administering legislation that facilitated, provided a framework and regulations that created the surrounding in which theatre operated as well as providing minimal funding. It has also been effective in facilitating the movement of local and international theatre artists into and out of Zimbabwe during the period under study (1985 to present date). Generally this promoted the development of community theatre. However it maintains that its role was negatively affected by the restructuring process it underwent in 1995, and worsened by the changing economic and political conditions after 2000. Due to those circumstances it has not been able to regularly disburse enough funding yet that is the biggest area of deficiency in the sector. Instead it is the donor community that has shouldered this aspect mostly, in some cases with the assistance of the NACZ, which in turn has promoted largely, the development of political and theatre for communication. Theatre artists are continuously aligning themselves to the expectations of the donor community.
Keywords: Arts council; theatre; arm's length; patron; engineer; architect; facilitator; theatre association